Atomic physics, optical technologies and medical physics, 10-11.02.2022.,Riga - 80th scientific conference at the University of Latvia (LU Atomfizikas un spektroskopijas institūts, 2022)
80th International Scientific Conference of the University of Latvia Section ‘Atomic physics, optical technologies and medical physics’ will be held by Institute of Atomic Physics and Spectroscopy (IAPS) on 10-11.02.2022. The section will present the recent results, achieved by IAPS researchers and the IAPS partners in the following research fields: optical phenomena in gas, liquid, solid state and biological samples, optical methods for diagnostics, chemical analysis and optical sensor technologies, quantum optics and telecommunication, modelling, novel nanomaterials and their biomedical applications. Total 27 abstracts.
Atomfizika, optiskās tehnoloģijas un medicīnas fizika
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics::Other physics::Optics; Research Subject Categories::NATURAL SCIENCES::Chemistry::Physical chemistry::Spectroscopy; Atomic physics; optical technologies; medical physics